Surra: Trypanosomiasis in Livestock is Potential as Zoonotic Disease - April Hari Wardhana; Dyah H Savitri (Indonesian Center for Animal Research and Development, 2018)
Trypanosoma evansi is one of blood protozoans having the most wide distribution region compared to other Trypanosome species. The parasite causes trypanosomiasis known as Surra. The disease may cause mortality to the infected animals. In general T evansi only attack animal and cannot infect humans due to apolipoprotein 1 (Apo L-1) in human serum. The protein possess trypanolitic activity feature against T. evansi and effectively eliminates the protozoa. However, the knowledge of Surra infecting animals changed because there were atypical human trypanosomiasis cases reported in some countries due to T. evansi. The human Surra case occurred in Vietnam demonstrated that person with Apo L-1 could be infected by T. evansi. There was resistant strain of T. evansi found which able to disrupt human immune system. This paper will discuss Surra cases in both humans and animals, including mechanism of Apo L-1 on eliminating the parasite. Surra cases in human and animal should be seriously concerned because Surra could be pontential zoonosis threating human health.